A novel approach for Generating Association Rules pattern matching Using improved Apriori with Regression Technique - Sarada, W; Kumar, P.V (International Journal of Computer Sciences and Engineering, 2025)
Association rule mining is an astoundingly basic and critical piece of data mining.It will be utilized to Figure the entrancing plans from exchange databases. Apriori count will be a champion among those for all intents and purposes built up computations from guaranteeing association rules, yet all the it require the bottleneck Previously, adequacy. In this article, we recommended a prefixed-itemset-based data structure to create visit itemset, with those help of the structure we made sense of how to improve the viability of the conventional Apriori computation